The Effect of Transcranial Direct Current Stimulation on Relapse, Anxiety, and Depression in Patients With Opioid Dependence Under Methadone Maintenance Treatment: A Pilot Study - Mohammad Sadeghi Bimorgh; Abdollah Omidi; Fatemeh Sadat Ghoreishi; Amir Rezaei Ardani; Amir Ghaderi; Amir Ghaderi; Hamid Reza Banafshe; Hamid Reza Banafshe (Frontiers Media S.A., 2020)
Background and ObjectivePatients under methadone maintenance therapy (MMT) are susceptible to several complications including mental disturbances and risk of relapse. The present study was designed to evaluate the effects of tDCS on relapse, depression, and anxiety of opioid-dependent patients under methadone maintenance treatment (MMT).MethodsIt was a randomized-clinical trial that conducted among 27 male patients referred to the outpatient addiction clinic of Ibn-e-Sina psychiatric hospital in Mashhad from July 2018 to May 2019. Participants were allocated to two treatment groups including intervention and sham groups. The intervention group received seven sessions of tDCS, in the F3 (cathode) and F4 (anode) areas of the brain, each one lasts 20 min, in two consecutive weeks. Depression, anxiety, and stress scale-21 (DASS-21) were measured before, during, and after the intervention in patients under MMT. Relapse on the morphine, cannabis, and methamphetamine was screened by urine dipstick tests of morphine, cannabis, and methamphetamine.ResultsDepression, anxiety, and stress of participants were significantly reduced in the intervention group compared with the control after the seventh session of tDCS (P < 0.001, P=0.01, and P=0.01, respectively). In addition, the relapse rate showed no significant changes between the two groups (P=0.33).ConclusionOverall, our study demonstrated that depression, anxiety, and stress of participants were significantly reduced after the seventh session of tDCS, but did not affect on the relapse rate. Therefore, it can be applied as a safe and effective technique to relieve mental disorder among receiving MMT.Clinical Trial Registrationhttp://www.irct.ir, identifier IRCT20180604039979N1.